THE APPLICATION OF GENERATIVE LEARNING MODEL BASED ON REMEDIAL INTEGRATION IN REDUCING STUDENT MISCONCEPTIONS - Haratua Tiur Maria Silitonga; Erwina Oktavianty; Jamilah Jamilah; Masti Panjaitan (Jurnal Pendidikan Matematika dan IPA, 2020)
This study was aimed to examine the effect of a remedial-integrated activity on dynamic fluids materials using generative learning to reduce student misconception in Senior High Schools (SMA). Pre-experimental method with the design of pretest-posttest control group was used in this study. This study was held in SMAN 7 Pontianak, West Kalimantan, involving the total number of 36 students from which were selected randomly at XI MIPA Class (Eleventh grade of Natural Science Class) using the random sampling with intact group technique. The instrument of this study used was the total question of a diagnostic test with 18 multiple-choice questionnaires. Then, the collected data was analysed using a descriptive statistic and t-test. The result of this study revealed that the remedial integration on Physics misconceptions positively decreased the levels of student misconceptions in Senior High Schools against dynamic fluids materials.